200k views
5 votes
(ab2 + 4a2 + 6a2b2) − (−ab2 + 2a2b2 + 4a2)

1 Answer

4 votes

For this case we have the following expression:


(ab ^ 2 + 4a ^ 2 + 6a ^ 2b ^ 2) - (- ab ^ 2 + 2a ^ 2b ^ 2 + 4a ^ 2) =

We must simplify taking into account that:


- * - = +\\- * + = -

So, we have:


ab ^ 2 + 4a ^ 2 + 6a ^ 2b ^ 2 + ab ^ 2-2a ^ 2b ^ 2-4a ^ 2 =

We add similar terms:


ab ^ 2 + ab ^ 2 + 4a ^ 2-4a ^ 2 + 6a ^ 2b ^ 2-2a ^ 2b ^ 2 =\\2ab ^ 2 + 4a ^ 2b ^ 2

Answer:


2ab ^ 2 + 4a ^ 2b ^ 2

User Mario Niepel
by
6.4k points